Upaya Mempertahankan Eksistensi Seni Kuntulan di Desa Kabunan Kecamatan Dukuhwaru Kabupaten Tegal - Vika Fitrotul Uyun; Bunga Himatul A’liyah; Leni Marlinah; Melinda Sabela Putri; Melli Nurul Aesyi; Mu’tamaroh (Profetik: Jurnal Pengabdian Masyarakat, 2024)
As a village rich in regional arts, Kabunan often sends its art groups to be displayed to the general public. The art inherent in the Kabunan village community is kuntulan art. Kuntulan art itself is an art that combines the Javanese art of flying music and the martial art of pencak silat. The art of kuntulan in Kabunan village is very embedded with the proven achievements of kuntulan art in Kabunan village at the district level. The potential for Kuntulan art to be passed on to children and grandchildren is enormous. However, some people don't understand the art of kuntulan and many don't know that in Kabunan village there is village potential, especially legendary traditional art. This is the key to the development of kuntulan art. Thus maintaining the existential value of kuntulan art. Until now, Kuntulan art is still often performed at large events. Only accompanied by Javanese flying and silat movements which are the aesthetic value of this traditional art. Therefore, we are students from a group of 12 villages in Kabunan sub-district. Dukuhwaru introduced the art of kuntulan to the wider community through interviews with the head of the kuntulan and the members who follow him. The suggestion for our activity aims to expand knowledge about kuntulan dance and introduce kuntulan art in Kabunan village.